Jafnrétti og mannauður : drög að jafnréttisáætlun fyrir Samskip - Guðrún Hauksdóttir 1966- (2013)
Verkefnið er lokað til 31.5.2050. This study discusses the advantages and the need for companies to adopt effective gender equality by looking through the gender glasses. The development of the equality laws in Iceland is reviewed as well as today’s status of gender equality in the country. Samskip, an Icelandic transportation company, is analyzed on the basis of equality and a proposition is made for an equality plan for the company. In this diverse and dynamic society in which we live it is more important than ever that companies develop equal opportunities and diverse strategies to attract the best people. Men and women are different, and to reach and retain the talented ones, companies need to recognize the needs of both genders. This can be achieved by utilizing skills and knowledge from both genders. The prevailing view is that diversity in management and team unity results in a more successful company. Women have different managerial potential than men which comes in handy when working with the diversity that characterizes the labor market today. Women are a major segment of the consumer market and play a large role in decision-making when it comes to purchasing. Companies should therefore also employ women in marketing to better recognize consumer needs. Many studies show that companies that have both sexes on their board yield higher returns than those who only include men. Keywords: Gender equality, equality plan, gender pay gap, gender segregation in the labour market, flexible work, gender glasses. Í þessari rannsókn er fjallað um kosti og nauðsyn þess að fyrirtæki taki upp virka jafnréttisstefnu með því að horfa í gegnum kynjagleraugun. Farið er yfir þróun jafnréttislaga á Íslandi og stöðu jafnréttis á Íslandi í dag. Greind er staða Samskipa í jafnréttismálum og lögð fram tillaga að jafnréttisáætlun fyrir fyrirtækið. Í því fjölbreytta og breytilega þjóðfélagi sem við lifum í er mikilvægara en nokkru sinni fyrr að fyrirtæki þrói jöfn tækifæri og fjölbreytta stefnu til að laða að besta ...